The role of using Kahoot application as a platform for learning Arabic to improve student's motivation at Islamic high schools "Arriyadlah" paiton probolinggo - Firda Safira; Muhammad Sugianto; Shobirin (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2026)
This study is motivated by the low motivation of students to learn Arabic, which stems from some teachers’ reliance on traditional methods and the limited use of technology-based teaching tools. The aim of this study is to investigate how the Kahoot app can be used as a teaching tool in Arabic language instruction and to demonstrate The role of using  Kahoot application as a platform for learning Arabic to improve student's motivation at Islamic high schools "Arriyadlah" paiton probolinggo. The study relied on the theoretical framework related to teaching methods, the Kahoot app as an interactive teaching tool, and learning motivation theory. The study employed a qualitative, descriptive approach. Data were collected through observation, interviews, and documentation, with the school principal, the Arabic language teacher, and the students serving as the primary sources of information. Data analysis was conducted through data reduction, presentation, and the derivation of results, with their validity verified using the triangulation method across sources and methods. The study’s results showed that the use of Kahoot! in Arabic language instruction requires the availability of appropriate facilities such as computers, internet access, and a projector, in addition to thorough preparation by the teacher and the selection of questions appropriate to the instructional material. The results also indicated that the use of Kahoot! contributes to increasing students’ activity, enthusiasm, and participation in the learning process, thereby enhancing their motivation to learn Arabic. Keywords: Kahoot app, digital educational media, Arabic language learning, student motivation.